2021
DOI: 10.3390/heritage4020046
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Liu Kang’s Paris Practice (1929–1932): Insight into Painting Materials and Technique

Abstract: This paper presents the results of an extensive study of 14 paintings by the pioneering Singapore artist Liu Kang (1911–2004). The paintings are from the National Gallery Singapore and Liu family collections. The aim of the study is to elucidate the painting technique and materials from the artist’s early oeuvre, Paris, spanning the period from 1929 to 1932. The artworks were studied with a wide array of non- and micro-invasive analytical techniques, supplemented with the historical information derived from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A close look at his container with tools revealed that the artist intended to execute the painting only with palette knives ( Figure 6 a). Although the broad underpaint of the composition appears to be typical for the artist’s initial approach to painting [ 6 , 13 ], further execution of the Huangshan and Guilin landscapes stands out from his earlier genres and artistic phases mainly due to the use of a limited palette of colours and a consistent shift towards rich texture as a way of artistic expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A close look at his container with tools revealed that the artist intended to execute the painting only with palette knives ( Figure 6 a). Although the broad underpaint of the composition appears to be typical for the artist’s initial approach to painting [ 6 , 13 ], further execution of the Huangshan and Guilin landscapes stands out from his earlier genres and artistic phases mainly due to the use of a limited palette of colours and a consistent shift towards rich texture as a way of artistic expression.…”
Section: Resultsmentioning
confidence: 99%
“…The adopted research strategy relied on the methods used by the authors in the previous investigation campaigns of Liu Kang’s paintings [ 6 , 13 , 16 ]. Such an approach ensured the consistency of the acquired data and their interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building this foundation of knowledge is the first step towards more focused studies, such as the ones reported by Lizun et al [8] and Martins et al [9]. Lizun et al take on the complex task of exploring the painting technique and materials adopted by Singapore artist Liu Kang during his period in Paris (1929)(1930)(1931)(1932), by analysing 14 paintings with a wide array of non-and micro-invasive analytical techniques [8]. The detailed technical examination is coupled with historical information derived from archives and contemporary catalogues.…”
Section: Sotiropoulou Et Al's Reviewmentioning
confidence: 98%
“…Moreover, the artist's painting practice was also impacted by financial difficulties or the lack of art materials. Therefore, to continue with his artistic development, he was forced to paint over earlier compositions (Lizun, 2021a;Lizun et al, 2021b;Lizun et al, 2021c;Lizun et al, 2021d).…”
Section: Research Articlementioning
confidence: 99%